1995
DOI: 10.1099/13500872-141-3-605
|View full text |Cite
|
Sign up to set email alerts
|

Reversible expression of motility and flagella in Clostridium chauvoei and their relationship to virulence

Abstract: CIostridium chau woei strain 0 ki nawa produced spontaneous non-mot i I e variants at an unusually high rate (approx. conditions without mutagen. Revertants of non-motile variants were detected at a rate of approximately lo-'. Biochemically, every variant corresponded well with the parental strain. By transmission electron microscopy, three of nine non-motile variants of strain Okinawa were found to be flagellate, while the other six were found to be aflagellate. These phenotypes were confirmed by Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Motility-defective, aflagellated bacteria have been reported to be affected in virulence because of abberations in their host adherence, invasion mechanism, or unknown factors. These include aflagellated Vibrio cholerae (Attridge and Rowley, 1983), Campylobacter jejuni (Wassenaar et al, 1991), Borrelia burgdorferi (Sadziene et al, 1991), Clostridium chauvoei (Tamura et al, 1995) a. Student's t-test was used to determine the probability (P ) that the difference between the paired mean numbers are significant.…”
Section: Discussionmentioning
confidence: 99%
“…Motility-defective, aflagellated bacteria have been reported to be affected in virulence because of abberations in their host adherence, invasion mechanism, or unknown factors. These include aflagellated Vibrio cholerae (Attridge and Rowley, 1983), Campylobacter jejuni (Wassenaar et al, 1991), Borrelia burgdorferi (Sadziene et al, 1991), Clostridium chauvoei (Tamura et al, 1995) a. Student's t-test was used to determine the probability (P ) that the difference between the paired mean numbers are significant.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, flagellum-based motility is one of the more common mechanisms used by motile organisms to move toward preferred sites for colonization typically in the earliest stages of the infection process. Thus, bacterial flagella have been considered an important virulence determinant and flagellum-deficient mutants of several pathogens have been shown to be avirulent (4,18,28,38,45). All bacterial flagella are helical macromolecular structures composed predominantly of a single highly conserved protein called flagellin.…”
mentioning
confidence: 99%
“…It has been suggested that the virulence of C. difficile strains is Clostridium difficile flagellin not solely attributable to toxin production ; other factors such as presence of flagella could contribute to virulence. The role of flagella in microbial pathogenesis factors such as virulence, adherence, invasiveness or colonization has been demonstrated for numerous bacteria (Grant et al, 1993 ;Scherer et al, 1993 ;Zhang et al, 1993 ;Grossman et al, 1995 ;Pruckler et al, 1995 ;Tamura et al, 1995 ;Milton et al, 1996 ;Mobley, 1996 ;Bosshardt et al, 1997 ;Kennedy et al, 1997 ;Rosalski et al, 1997 ;West et al, 1997 ;Feldman et al, 1998). In our experiments in vitro, no inhibition of adherence was shown with antibodies against the recombinant flagellum subunit.…”
Section: Discussionmentioning
confidence: 99%